2012
DOI: 10.1590/s1806-00132012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Reconhecimento da dor no recém-nascido por alunos de medicina, residentes de pediatria e neonatologia

Abstract: SUMMARY BACKGROUND AND OBJECTIVES:Learning about the painful phenomenon during medical qualification shapes future clinical practice. This study aimed at evaluating the perception and understanding of pain in neonates (NN) by medical students, residents in Pediatrics and Neonatology. METHOD: Cross-sectional study with 180 students from the 1 st to the 6 th year of medicine, 42 residents in Pediatrics and 20 residents in Neonatology, from 2009 to 2010. Twelve theoretical questions about NN pain were applied. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Studies [5][6][7][8][9][10][11] have highlighted that the fragmented and deficient practices of physicians and nurses focused on the assessment and treatment of pain in neonatal units are due to gaps in the education and training received, despite current international guidelines 3,4 indicating the use of non-pharmacological and pharmacological strategies for the NB. This study found a lack of evidence-based protocols and guidelines for the assessment of pain, with the use of scales, and employment of systematized non-pharmacological and pharmacological measures for the relief of the pain of the NB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [5][6][7][8][9][10][11] have highlighted that the fragmented and deficient practices of physicians and nurses focused on the assessment and treatment of pain in neonatal units are due to gaps in the education and training received, despite current international guidelines 3,4 indicating the use of non-pharmacological and pharmacological strategies for the NB. This study found a lack of evidence-based protocols and guidelines for the assessment of pain, with the use of scales, and employment of systematized non-pharmacological and pharmacological measures for the relief of the pain of the NB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [5][6][7][8][9][10][11] have shown that there is a gap in the application of scientific knowledge in the clinical practice by health professionals, particularly with regards to the management of neonatal pain. While there are valid and reliable scales for the assessment of pain, and effective non-pharmacological and pharmacologic strategies to treat the pain, the undertreatment of pain in NBs is still a problem in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this study might have been the establishment of working time of "three months or longer". It was noted that the more qualified is the pediatrics or neonatology professional, there is significant increase in knowledge, especially about pain matters 9 . A UK study has shown that some professionals (1.5%) disagreed that a premature with less than 28 weeks would feel pain 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances have increasingly enabled the survival of very premature or very sick infants (6) . In the context of nursing care, non-pharmacological measures are highlighted as a strategy of care for pain relief, such as the use of music (4,7) and 25% glucose (8) .…”
Section: Introductionmentioning
confidence: 99%
“…X 1 = Average score; SD 2 = Standard deviation; IL 3 = Inferior limit; SL 4= Superior limit; 5 F= Difference of means;6 Bonferroni Test…”
mentioning
confidence: 99%